Analysis of the importance of using intermediate intervals in the calculation of geometrical characteristics of the ship’s hull - Paweł Chorab; Dorota Łozowicka (PLoS ONE, 2026)
This article examines the impact of incorporating intermediate sections in geometric hull calculations and highlights their role in improving the accuracy of underwater volume estimation and the determination of the center of buoyancy. The study demonstrates that neglecting intermediate sections can lead to substantial numerical errors, which may affect the reliability of hydrostatic parameters used in stability assessment. In the context of hydrodynamic analyses, accurate geometric representation remains essential for obtaining consistent and reproducible results. The presented results quantitatively assess the reduction of numerical integration error achieved by introducing intermediate sections and by comparing selected classical numerical integration schemes. Based on these findings, a genetic algorithm–based optimization framework is proposed as future work to support the automated selection of the number and spatial distribution of intermediate sections, as well as the integration strategy, while balancing accuracy and computational cost. The proposed framework is intended to provide a systematic approach for adapting hull discretization to local geometric characteristics and to support reproducible hydrostatic calculations in engineering applications.